Influence of vacuum preloading on vertical bearing capacities of piles installed on coastal soft soil. Issue 7 (9th August 2019) - Wang, Jun; Zhou, Zhi; Fu, Hongtao; Dong, Quanyang; Cai, Yuanqiang; Hu, Xiuqing
Abstract: Land reclamation has increased significantly in the eastern coastal areas of China. The increased exploitation of offshore resources has made cast- in-situ piles more preferable in these regions. However, precise prediction of axial forces and shaft resistances of piles is particularly difficult because geological conditions are complex after the foundation is treated by vacuum preloading. In this study, two groups of cast- in-situ piles, each of which consisted of two piles installed in soft soil in Oufei Project, Wenzhou, China, were compared by conducting tests using the slow static loading method to evaluate the influence of applying vacuum preloading to deal with soft soil foundation on the vertical bearing capacities of the piles. Two piles were located in an untreated area, while the other two were located in a vacuum preloading treating area. All the piles had the same length and diameter. In addition, the axial forces and shaft resistances of piles were calculated based on the measured strains. The field tests revealed that the ultimate bearing capacities and shaft resistances of test piles were significantly improved compared to those of the piles in untreated area. The experimental results presented in this study are expected to be highly beneficial for practical engineering.